2021
DOI: 10.3390/jcm11010221
|View full text |Cite
|
Sign up to set email alerts
|

Updates in Clinical and Translational Glaucoma Research

Abstract: Glaucoma is a sight-threatening disease and the primum mobile of irreversible blindness worldwide [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Changes leading to a reduced density and calibre of retinal blood vessels occur during glaucoma [1,[6][7][8]. Numerous studies using optical coherence tomography angiography (OCTA) have shown significant reductions in the flow density, flow index, and vessel density in the optic nerve head and macula in patients with glaucoma compared to controls, as well as the association between these parameters and changes in the visual field [6,[9][10][11][12]. Colour Doppler Imaging has demonstrated reduced velocities and an increased resistivity index in intraocular vessels in glaucoma patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…Changes leading to a reduced density and calibre of retinal blood vessels occur during glaucoma [1,[6][7][8]. Numerous studies using optical coherence tomography angiography (OCTA) have shown significant reductions in the flow density, flow index, and vessel density in the optic nerve head and macula in patients with glaucoma compared to controls, as well as the association between these parameters and changes in the visual field [6,[9][10][11][12]. Colour Doppler Imaging has demonstrated reduced velocities and an increased resistivity index in intraocular vessels in glaucoma patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is defined by the optic nerves' specific appearance and visual field disturbances. Glaucoma is the second leading cause of blindness and the leading cause of irreversible blindness worldwide [ 1 , 2 ]. Although various factors are associated with the pathogenesis of this disease, the exact mechanism needs to be further understood and studied.…”
Section: Introductionmentioning
confidence: 99%